Tritium Water Distillation Assisted with Adsorption and Isotopic Exchange. (3rd April 2017) - Miho, Y.; Fukada, S.; Motomura, T.; Mizutani, J.; Hirano, S.; Arimoto, M.; Takeuchi, T.
Abstract: Water distillation packed with materials having adsorption ability is proposed for wastewater detritiation, and behavior of HTO depletion or enrichment is experimentally investigated. It is proved that the apparent volatility ratio of H2 O-to-HTO is increased by an isotopic effect on adsorption under a steady-state operation. Danckwerts' surface renewal model is applied to explain the T enrichment process in a lab-scale water distillation column. The effect is estimated in terms of an adsorption enhancement factor included in the T separation factor, εHT, ad, which depends on the kinds of adsorbents and liquid-vapor flow conditions. The value of the enhancement factor is also confirmed εHT, ad  = 1.02 in a comparatively large-scale distillation operation packed with Sulzer packing or Raschig ring coated with zeolite adsorbent. A large-scale distillation tower can be designed to detritiate radioactive wastewater generated in Fukushima's Daiichi NPS based on the present experimental results.